Controlled Synthesis, Characterization and Magnetic Properties of Unsymmetrical Heterodinuclear CuIIMII (M = Co, Mn and Cd) Complexes in Alkoxo Bridged Acyclic Ligand Environment - Ghosh, Dipesh (Asian Journal of Chemistry, 2020)
This work reports the syntheses of heterodinuclear Cu(II)-Co(II), Cu(II)-Mn(II) and Cu(II)-Cd(II) complexes following a convenient single-pot synthetic procedure using the two asymmetric binucleating ligands. Site-specificity offered by one of the ligands' arms towards Cu(I) center has been successfully exploited here, avoiding all sorts of impending scrambling reactions. X-ray crystallography and ESI-mass spectral studies have been used to prove the exclusivity of these products. Magnetic studies at variable temperatures (4-300 K) have been proved inadequate to assign any spin-ground state for Cu(II)-Co(II) and Cu(II)-Mn(II) compounds.